Early neurological wake-up test in intubated patients with traumatic brain injury - Meng Jiang; Chang-li Li; Xiao-peng Wu; Xing-chen Lin; Yuan-run Zhu; Li-gang Xu; Xiao-feng Yang (International Journal of Emergency Medicine)
Abstract Background Daily wake-up has been implemented widely in intensive care units (ICU) and could improve the patients’ prognosis. However, little is known about the benefit of early neurological wake-up test (ENWT) in patients with acute traumatic brain injury (TBI). We aimed to investigate the role of ENWT as a clinical monitoring tool for TBI and its association with prognosis. Methods This is an observational retrospective study included intubated and continuously sedated TBI in ICU, and all data were extracted from three tertiary hospitals from China. The main exposure of interest was ENWT, defined as cessation of sedation within 24 h after admission. The primary outcome was 28-day mortality. Propensity score matching (PSM) was performed at a 1:1 ratio. Multivariable analyses were further used to adjust for residual confounders. Results The pre-matched and propensity score-matched cohorts included 1386 and 704 patients, respectively. In the PSM analysis, 28-day mortality was 24.7% (87/352) in the ENWT group and 37.2% (131/352) in the control group. ENWT was associated with lower 28-day mortality (hazard ratio [HR], 0.57; 95% CI, 0.44–0.76; P < 0.001). ENWT was also associated with lower in-hospital mortality (odds ratio [OR], 0.54; 95% CI, 0.38–0.77; P = 0.001), and higher discharge-home rate (OR, 1.83; 95% CI, 1.19–2.83; P = 0.006). A sensitivity analysis using the entire cohort also demonstrated lower 28-day mortality (HR, 0.58; 95% CI, 0.44–0.75; P < 0.001). However, it should be noted that ENWT was related to a higher rate of delirium during ICU stay (OR, 1.66; 95% CI, 1.21–2.26; P = 0.001). Further analysis demonstrated that tracheostomy during ICU stay led to a significant difference in 28-day mortality. Conclusion ENWT was associated with a lower risk-adjusted 28-day mortality in acute TBI patients. A higher rate of tracheostomy may partly contribute to this relationship.